Mitochondrial respiration in peripheral blood mononuclear cells of healthy adult population - John H. Lee; Jacob Vine; Lakshman Balaji; Natia Peradze; Nivedha Antony; Yanbo Wang; Andrea Morton; Ari Moskowitz; Michael W. Donnino; Xiaowen Liu (PLoS ONE, 2026)
Given the potential for mitochondrial medicine as a therapy in various illnesses, mitochondrial tests derived from blood samples have gained increasing value. The aim of this study was to perform an in-depth investigation of mitochondrial respiration in peripheral blood mononuclear cells (PBMCs) of healthy adult participants to characterize mitochondrial respiration in health. Adult participants without acute illness were recruited. PBMCs were isolated and quantitative, real-time measurements of mitochondrial oxygen consumption rate were performed using the Seahorse XF Cell Mito Stress Test Kit with Seahorse XFe96 Analyzer. The study included 184 participants without previously diagnosed medical conditions. There was no association between mitochondrial respiration and sex and age groups (≤ 30 years vs. > 30 years). Maximal and Spare respirations were associated with body mass index (BMI). The findings of this study contribute to the growing body of knowledge on mitochondrial bioenergetics in healthy adults and provide further insights into its association with demographic and anthropometric factors.